The little green data book ... : from the World development indicators ... - World Bank; World Bank. International Economics Department. Development Data Group; World Bank. Environment Department; World Bank. Development Data Group (Washington, D.C. : International Bank for Reconstruction and Development/The World Bank, 2001)
This data book is a knowledge resource that aids policy makers in using environmental data more effectively to support priority-setting and improve development outcomes.
Also issued online.
Drawn from: World development indicators, presenting environmental statistics in a format similar to the: Little data book, which presents demographic and economic statistics from the same source.
Issued jointly by: Development Economics Data Development Group; and: Environment Dept; <2004-> issued by: Data Development Group; and: Environment Department of the World Bank.
Description based on: 2011.
Latest issue consulted: 2011.
oif 14/05/14
Keywords: Economic history -- 1990- -- Statistics -- Periodicals; Land use -- Statistics -- Periodicals; Economic development -- Statistics -- Periodicals; Economic indicators -- Periodicals; Environmental indicators -- Statistics -- Periodicals